Comparison between laser and transobturator tape therapy in the treatment of stress urinary incontinence and role of overweight in treatment: a prospective observational study - Yilmaz, Feray Cagiran; Acik, Murat; cagiran, Fatma (Springer London Ltd, 2023)
Introduction and hypothesisStress urinary incontinence (SUI) is treated with transobturator tape (TOT) sling procedures, but problems arise with artificial mesh in certain instances. Hence, non-invasive laser therapy may be useful under such circumstances. The current study was aimed at comparing the effects of these two treatments and at checking their applicability in various body mass index (BMI) groups.MethodsSeventy-nine patients, who were clinically diagnosed with SUI, were divided into two groups, those who preferred TOT and those who preferred the transvaginal fractional micro-ablative CO2 laser system. The SUI symptoms and International Consultation on Incontinence Questionnaire Short Form (ICIQ-SF) scores of the patients were determined before and at the 12th month after the treatment. General linear model, Stuart-Maxwell, and Bonferroni correction for pairwise comparison analyses were performed to compare the efficacy of the treatment type.ResultsThe ICIQ-SF score decreased by 56.8% for laser therapy and 43.5% for TOT therapy (mean & PLUSMN; SE = 5.97 & PLUSMN; 0.16 and 5.09 & PLUSMN; 0.14 respectively). Laser therapy had a better effect on ICIQ-SF than TOT therapy (& eta;2p: 0.176, p(time*group) < 0.001). Regardless of the types of treatment, the ICIQ-SF scores of healthy-weight participants decreased more than those of overweight participants (& eta;2p:0.050, p(time*group) = 0.045). In the TOT group, healthy-weight participants were more than twice as likely to recover fully from SUI symptoms as overweight participants, 1 year after the treatment. In the laser group, the majority of healthy-weight participants (88.8%) did not report any SUI symptoms after the treatment.ConclusionsThe efficacy of laser therapy for urinary incontinence was confirmed. Furthermore, it was observed that being overweight may be a risk factor for the failure of laser therapy.
Keywords: Stress urinary incontinence; Transvaginal fractional micro-ablative CO2 laser system; Quality of life; Overweight